A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males - Gonçalves, Clayton C.; Domahovski, Alexandre C. (European Journal of Taxonomy, 2021)
A new Brazilian leafhopper genus of the subfamily Neocoelidiinae is proposed: Takiyaella gen. nov. based on T. sexguttata (Chiamolera & Cavichioli, 2003) gen. et comb. nov. and five new species: T. anomala gen. et sp. nov., T. coelhomarquesae gen. et sp. nov., and T. daniela gen. et sp. nov. from the state of Rio de Janeiro; T. cavichiolii gen. et sp. nov. from the state of Paraná, and T. mejdalanii gen. et sp. nov. from the state of Minas Gerais. A distribution map and identification key to Takiyaella species are provided.